Genetic and modifying factors that determine the risk of brain tumors - de Cresci Braga Montelli, Terezinha [UNESP]; Peraçoli, Maria Terezinha Serrão [UNESP]; Rogatto, Silvia Regina [UNESP]; Kaneno, Ramon [UNESP]; do Prado, Cíntia Helena Braga Montelli [UNESP]; de Medeiros Cardassi Rocha, Patrícia [UNESP] (Bentham Science Publishers, 2011)
Some modifying factors may determine the risk of brain tumors. Until now, it could not be attempted to identify people at risk and also to improve significantly disease progression. Current therapy consists of surgical resection, followed by radiation therapy and chemotherapy. Despite of these treatments, the prognosis for patients is poor. In this review, we highlight general aspects concerning genetic alterations in brain tumors, namely astrocytomas, glioblastomas, oligodendrogliomas, medulloblastomas and ependymomas. The influence of these genetic alterations in patients' prognosis is discussed. Mutagen sensivity is associated with cancer risk. The convincing studies that linked DNA damages and DNA repair alterations with brain tumors are also described. Another important modifying factor is immunity. General immune response against cancer, tumor microenvironment and immune response, mechanisms of tumor escape, CNS tumor immunology, immune defects that impair anti-tumor systemic immunity in brain tumor patients and local immunosuppressive factors within CNS are also reviewed. New hope to treatment perspectives, as dendritic-cell-based vaccines is summarized too. Concluding, it seems well established that there is association between brain tumor risk and mutagen sensivity, which is highly heritable. Primary brain tumors cause depression in systemic host immunity; local immunosuppressive factors and immunological characteristics of tumor cells may explain the poor prognosis and DNA damages responses can alert immune system. However, it is necessary to clarify if individuals with both constitutional defects in immune functions and genetic instability have higher risk of developing brain tumors. Cytogenetic prospective studies and gene copy number variations analysis also must be performed in peripheral lymphocytes from brain tumor patients. © 2011 Bentham Science Publishers Ltd.
Keywords: Adaptive immunity; Brain tumors; Cellular immunity; Dendritic cell-based vaccines; DNA copy number variations; DNA repair; Innate immunity; antineoplastic agent; dendritic cell vaccine; astrocytoma; blood brain barrier; brachytherapy; brain infection; brain tumor; cancer adjuvant therapy; cancer immunology; cancer risk; carcinogenesis; dendritic cell; DNA damage; ependymoma; gene dosage; gene mutation; genetic analysis; genetic association; glioblastoma; heredity; human; immune deficiency; immune response; lymphocyte; medulloblastoma; nonhuman; oligodendroglioma; prognosis; review; T lymphocyte; tumor escape; tumor microenvironment; Blood-Brain Barrier; Brain Neoplasms; Chromosome Aberrations; Dendritic Cells; Disease Progression; DNA Copy Number Variations; Humans; Immune System; Immunotherapy; Neoplastic Stem Cells; Risk Factors; Tumor Escape; Tumor Microenvironment